Infiltrating/sealing proximal caries lesions: A 3-year randomized clinical tria (2012)
This randomized split-mouth controlled clinical trial aimed at assessing the therapeutic effects of infiltration vs. sealing for controlling caries progression on proximal surfaces. Out of 90 adult students/patients assessed at university clinics and agreeing to participate, 39, each with 3 proximal lesions identified radiographically around the enamel-dentin junction to the outer third of the dentin, were included. Lesions were randomly allocated for treatment to test-A (Infiltration: ICON-pre-product; DMG), test-B (Sealing: Prime-Bond-NT; Dentsply), or control-C (Placebo). Primary outcome after 1, 2, and 3 yrs of radiographically observed lesion progression was assessed by an independent examiner blinded to groups, using pair-wise and digital-subtraction readings. No adverse events occurred. In 37 participants assessed after 3 yrs, 10 lesions (A-4; B-2; C-4) progressed deep into dentin and needed operative treatment. The 3-year therapeutic effect, based on pair-wise radiographic readings between infiltration and placebo, was 37.8% (95%CI: 20.5-55.2%) and that between sealing and placebo was 29.7% (95%CI: 20.2-35.0%). One-year follow-up digital-subtraction readings showed significant differences in lesion progression between infiltration and placebo (P = 0.0012) and between sealing and placebo (P = 0.0269). The study showed that infiltration and sealing are significantly better than placebo treatment for controlling caries progression on proximal lesions. No significant difference was seen between infiltration and sealing (ClinicalTrials.gov number CT01417832).